Case report: Successful treatment with spesolimab of acrodermatitis continua of Hallopeau in an older patient without IL36RN mutations - Zheng, Jianfeng; Ding, Yangfeng; Shi, Yuling; Yi, Xuemei (Frontiers in Immunology, 2025)
BackgroundAcrodermatitis continua of Hallopeau (ACH) is a rare, sterile pustular psoriasis variant refractory to many conventional treatments. The eruption typically occurs after local trauma or infection; other etiologies include neural, inflammatory, and genetic causes. Herein we reported a single case of a 64-year-old patient with ACH that was successfully treated with spesolimab for 19 weeks.Case summaryA 64-year-old Chinese male with no personal or known family history of psoriasis had recurrent episodes of redness, swelling, and pustules in the nail bed on seven fingers with progressive degeneration of the nails. The patient was monitored as to the evolution of the disease over half of a year before he referred his case to our attention. A diagnosis of ACH was made, allowing for the administration of local steroids and oral acitretin. However, after 3 months of acitretin treatment, no improvement was observed. In December 2023, this patient came to our inpatient department; his modified nail psoriasis severity index score was 32. Before starting treatment, a comprehensive set of laboratory and instrumental tests were all found to be negative. Moreover, whole-exome sequencing was performed in our patient, and it revealed no rare coding variant in IL36RN, CARD14, or AP1S3. Therefore, the patient was administrated with a dose of 900 mg spesolimab. After 10 days, the patient showed a significant decrease in discomfort and pain. In order to strengthen the therapeutic effect, he was given the second dose of 900 mg spesolimab after 4 weeks. After 19 weeks of spesolimab treatment, the patient’s nail lesions showed complete resolution, and no adverse effects were reported.ConclusionThe case report suggests that spesolimab may offer significant therapeutic benefits for ACH.